Hierarchical porous nanostructures assembled from ultrathin MnO2 nanoflakes with enhanced supercapacitive performances - Jiang, Hao (2013)
Three kinds of hierarchical porous nanostructures assembled from ultrathin MnO2 nanoflakes with different sizes and crystallinities, have been synthesized by a very simple and scalable strategy. When applied as electrode materials for supercapacitors, all of them exhibited enhanced electrochemical performances due to the high utilization of active materials. More significantly, based on these ultrathin nanostructures, we have discussed the relationships between their specific areas, pore sizes and crystallinities and their electrochemical performances. Among them, the product synthesized in an ice bath with an especially high specific area (269 m2 g−1), uniform pore size distribution (5.1 nm) and poor crystallinity, exhibited the highest specific capacitance (328 F g−1) with a high rate and cycling stability. It is thought that the hierarchical ultrathin porous nanostructures can serve as promising electrode materials for supercapacitors.